HIGIENE SANITASI PENGELOLAAN MAKANAN DAN PERILAKU PENJAMAH MAKANAN DI KANTIN SEKOLAH MENENGAH ATAS (SMA) NEGERI DAN SWASTA DI KECAMATAN RANTAU UTARA KABUPATEN LABUHAN BATU TAHUN 2012 - Nurmala Sari; Irnawati Marsaulina; Indra Chahaya (Lingkungan dan Kesehatan Kerja, 2013)
Management of food hygiene sanitation and behaviors foodhandlers in the school canteen of public and private high schools in the district of North Rantau Labuhan Batu in 2012. Canteen is one of the most important facility  school in terms of building a quality generation. Management of food hygiene sanitation behavior of food handlers in school is important in order to get a guaranteed food clean so that the students can live healthily and avoid health problems. The purpose  this research was determine the state the management of food hygiene sanitation and behaviors foodhandlers in the school canteen public and private high schools in the district of North Rantau Labuhan Batu. The research was a descriptive survey in order to get an description the state of the management of food hygiene sanitation in the school canteen and to description the behavior of foodhandlers in the management of canteen food. The results showed that the variables of location and physical condition of buildings, as well as the 6 principles management of food hygiene sanitation have already qualified while sanitary facilities, kitchen, dining and food warehouse and foodhandlers are not eligible. For the behavior was found most food handlers in school canteen was knowledgeable, had good attitudes, and majority of the food handlers fell onto the good food handling category. The conclusion is that the physical condition of the site and buildings,equipment and food handlers, and six principles of hygiene and sanitation from the seven school already qualified, while sanitary facilities, kitchen not yet qualified. As for the behavior of food handlers, it was found that the handlers were knowledgeable, had good attitude, and took good actions. Based on these results it is expected that the school and canteen owners to further improve sanitation facilities that support the management of food hygiene sanitation, and improve the behavior of food handlers on food sanitation. Key words: Hygiene Sanitation food , Behavior foodhandlers